(untitled) (Medicine Today, 2024)
Introduction: The most important cause of maternal and perinatal morbidity and mortality are hypertensive disorder (Preeclampsia and eclampsia). In preeclampsia and eclampsia there is hypercoagulable state which acts as a risk factor for thromboembolism and DIC. Objective: This study was carried out to compare the coagulation indices in normal pregnancy, preeclampsia and eclampsia. Materials and Methods: This cross sectional study was conducted in Dhaka Medical College from January to December’ 2014. Total 150 women aged 18 – 40 years were selected for this study. Among them 50 normal pregnant, 50 preeclamptic and 50 eclamptic women were selected as study group and age matched 50 healthy nonpregnant women were considered as control group. Bleeding time was estimated by Duke’s method and clotting time was estimated by capillary tube method. Results: In this study bleeding time and clotting time were significantly higher in preeclamptic and eclamptic women than those of healthy nonpregnant women. Conclusion: From this study it can be concluded that bleeding time and clotting time are closely related with preeclampsia and eclampsia. Medicine Today 2023 Vol.36 (1): 41-44